Within the Classroom Doors: Unveiling the Lived Experiences of General Education Teachers in Handling Learners with Special Educational Needs - Balgos, Lionelle Rei; Nora Jovina Albores (Universitas Nahdatul Ulama Surabaya, 2024)
General education teachers are professionals equipped to teach learners in general education classrooms. However, due to the insufficient number of qualified special education teachers and the rising number of students with disabilities, these teachers are compelled to handle learners with special needs. This study aimed to explore and understand the lived experiences of general education teachers in handling learners with special educational needs. The researcher employed qualitative research, particularly phenomenological design. Seventeen teachers were purposively chosen and interviewed through in-depth interviews and focus group discussions, using a validated interview guide. Thematic analysis was employed to identify patterns of themes in the interview data. The results showed that teachers collectively experienced challenges in instructional skills, negative attitudes toward work, uncooperative parents, behavioral issues, and the responsibilities of teaching learners with special educational needs. An analysis of participants' responses revealed that teachers overcame challenges by self-up-skilling through internet resources, demonstrating adaptability, utilizing support systems, and maintaining strong faith in God. The participants shared insights on the belief that teaching is a noble profession and the need for special education training and seminars for non-special education teachers.